핑크색 절화용 거베라 신품종 ‘연화’ 육성 - 박재석(Jae Suk Park); 장성원(Sung Won Jang); 김현순(Hyun Sun Kim); 강희훈(Hyu Hyun Kang); 김창길(Chang Kil Kim); 정재동(Jae Dong Chung) (Weon'ye gwahag gi'sulji, 2007)
경북영주시 농업기술센터에서 ‘Beauty’를 모본, 흰색의 중형인 ‘Ansofie’를 부본으로 하여 2001년부터 2003년까지 교배 및 계통선발을 하였다. 2003년부터 2005년까지 3회의 특성검정을 거쳐서 거베라 신품종 ‘Yeunhwa’를 개발하였다. ‘Yeunhwa’는 화색이 선명하고 핑크색의 절화용으로 화형이 안정된 반겹꽃의 중륜화 품종이다. 3개년 평균 절화수량은 본당 70.0본/년으로 대비품종인 ‘로잘린’(51.5본/년)에 비해 35.9% 증수되었다. 그리고 절화수명은 7.5일로 나타났다. 특히 겨울철 저온에 강한 특성을 지니고 있어 월동 후 생존율이 대비품종인 ‘로잘린’에 비해 높았다. A new bright pink gerbera (Gerbera hybrida Hort.) ‘Yeunhwa’ was developed by crossed ‘Beauty’ and ‘Ansofie’ at Yoengju Agricultural Technology Extention Center. One breeding line, 2001-20, was selected in 2000 based on flower color and productivity on the first selection. A backcrossed line, 2002-202, was selected by crossing ‘2001-20’ and ‘Ansofie’ on Daegu, Suwon and Yoengju Agricultural Technology Extention Center in 2001. Characteristics trials were conducted three times from 2003 to 2005. Bred cultivar ‘Yeunhwa’ showed pink color (RP 62-A), green center, semi-double type and middle size flower with stable flower shape. The average productivity for three years was 70.0 stems per plant and increased 35.9% compared to that of cultivar ‘Rozalin’ which showed 51.5 stems. The vase life was 7.5 days. After winter season, the survival rate of cultivar ‘Yeunhwa’ was higher than that of cultivar ‘Rozalin’. KCI Citation Count: 8